Improving student learning outcomes in science subjects through a multiple intelligence approach - Wafiroh, Wafiroh (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study is to improve student learning outcomes in science subjects in fifth grade elementary school using the multiple intelligence approach. The research conducted is Classroom Action Research (CAR). for two cycles. Stages of each the cycle is planning, implementation, observation and reflection. Based on the results of research conducted using the multiple intelligence approach, it shows maximum results and students learn to be more effective, enthusiastic and fun at each meeting. because student learning outcomes are marked by the results of research detailed from the initial data, they get a complete score above the KKM 70 with a percentage of 30% and incompletely reach a value below the KKM 70 with a percentage of 70% while in the first cycle, the complete score above the KKM 70 reached a percentage of 50% and the incomplete score below the KKM 70 score got a 50% percentage and the second cycle got a complete score above the KKM 70, which was 90% while the incomplete score reached the KKM 70 that is 10%. These results indicate that using a multiple intelligence approach can improve student learning outcomes especially in science subjects at SD Negeri Prapag Lor 02